Hubungan Shift Kerja, Merokok, Dan Konsumsi Kafein Terhadap Kejadian Insomnia Pada Anggota Polisi Direktorat Sabhara Polda Bali - Padmayanni, Ni Putu Cesya; Adiwibawa, Danang Nur; Wiatma, Deny Sutrisna; Priono, Risky Irawan Putra (Jurnal Penelitian dan Kajian Ilmiah Kesehatan Politeknik Medica Farma Husada Mataram, 2025)
Insomnia is a sleep disorder that is commonly experienced by various age groups, including police officers who work in shifts, have smoking habits and consume caffeine. This third factor affects circadian rhythm and sleep quality, thus contributing to the incidence of insomnia. This study aims to analyze the relationship between work shifts, smoking and caffeine consumption on the incidence of insomnia in police officers from the Sabhara Directorate of the Bali Regional Police. This study used a cross-sectional design with 90 police officers as a sample. Data was collected using a questionnaire regarding work shift patterns, smoking habits, caffeine consumption, and insomnia levels using the Pittsburgh Sleep Quality Index (PSQI). Data analysis includes univariate and bivariate analysis. The results showed that night work shifts, smoking habits > 4 cigarettes/day, and caffeine consumption > 2 times/day significantly increased the risk of insomnia. In conclusion, work shifts, smoking and caffeine consumption are closely related to the incidence of insomnia in police officers. Prevention efforts are needed through education on healthy work patterns, smoking cessation programs, and managing caffeine consumption.